Effect of pH in The Biosynthesis of Gold Nanoparticles: A Review - Nawal Abdurazq Ahmad; Kawther Adaila; Abdounasser Albasher Omar (African Journal of Advanced Pure and Applied Sciences, 2023)
This review aimed to investigate the effect of pH on morphology, and size of gold nanoparticles (AuNPs) biosynthesized using extracts of various plant parts and agricultural waste. By reviewing previous studies, it was found that the formation of AuNPs was more rapid in neutral and basic mediums than in acidic mediums. Furthermore, most of those studies indicated that the smallest sizes of biosynthesized AuNPs, produced by plant extracts, were in neutral and alkaline mediums. Regarding the morphology, it was found that multiple shapes of the AuNPs were obtained in an acidic medium of the reaction, while there was typically a dominant shape of the AuNPs in the basic medium. In conclusion, significant quantities of AuNPs with appropriate sizes and morphology could be obtained by controlling the medium of the reaction when AuNPs are biosynthesized using extracts of plant parts and agricultural waste.